2014
DOI: 10.1093/jnci/dju053
|View full text |Cite
|
Sign up to set email alerts
|

DRAGO (KIAA0247), a New DNA Damage–Responsive, p53-Inducible Gene That Cooperates With p53 as Oncosuppressor

Abstract: DRAGO represents a new p53-dependent gene highly regulated in human cells and whose expression cooperates with p53 in tumor suppressor functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…KIAA0247 expression is suggested to be regulated by the tumor suppressor p53 and thus may be involved in carcinogenesis. Previous studies have shown that low KIAA0247 mRNA levels in feces strongly correlate with colorectal tumor size and poor prognosis and that KIAA0247 expression inversely correlates with tumor stage in ovarian cancer and histological grade in glioma . Therefore, we hypothesized that KIAA0247 may also play an important role in the progression of NSCLC.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…KIAA0247 expression is suggested to be regulated by the tumor suppressor p53 and thus may be involved in carcinogenesis. Previous studies have shown that low KIAA0247 mRNA levels in feces strongly correlate with colorectal tumor size and poor prognosis and that KIAA0247 expression inversely correlates with tumor stage in ovarian cancer and histological grade in glioma . Therefore, we hypothesized that KIAA0247 may also play an important role in the progression of NSCLC.…”
Section: Discussionmentioning
confidence: 96%
“…In KIAA0247 knockdown experiments, cells were transfected with KIAA0247 ‐specific siRNA and scrambled control siRNA (GenePharma, Shanghai, China) for 48 hours. For KIAA0247 overexpression, cells were transfected with a KIAA0247 expression plasmid and the corresponding empty pCNA3.0 vector, which were kindly donated by Massimo Broggini (Istituto di Ricerche Farmacologiche, Ranica, Italy) …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations